1981
DOI: 10.1159/000115275
|View full text |Cite
|
Sign up to set email alerts
|

Myasthenia gravis following Viral Infection

Abstract: The pathogenesis of myasthenia gravis is autoimmune, the real etiology, however, remains unknown. Virus has been suggested as an etiological agent of the disease. In this study we present 5 myasthenic patients, whose symptoms began a few weeks after a proven viral infection. The possibility of viral infection as etiology of myasthenia gravis is raised, and the mechanisms discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1984
1984
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“… Excess production of a highly specific pathogenic IgG autoantibody by autoreactive B2 cell clones as, for example, in myasthenia gravis ( 108 ). Expansion of such B2 cell clones could have been driven by antigen, e.g., with cross-reactive micro-organisms in patients without thymoma ( 109 ) or be driven by acetylcholine receptor specific autoreactive helper CD4 + T cells in thymoma-associated myasthenia gravis where such autoreactive T cells have escaped tolerance mechanisms ( 110 , 111 ). Deficiency of IgM-NAA, especially IgM-NAA with anti-idiotypic activity to a specific IgG autoantibody, thus incompletely neutralizing the increase in pathogenic IgG autoantibodies, such as antibodies to neutrophil cytoplasmic enzymes (myeloperoxidase, proteinase 3), which are commonly referred to as ANCA, dsDNA, and glomerular basement membrane (GBM) that are present in normal individuals ( 31 , 50 , 87 , 112 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… Excess production of a highly specific pathogenic IgG autoantibody by autoreactive B2 cell clones as, for example, in myasthenia gravis ( 108 ). Expansion of such B2 cell clones could have been driven by antigen, e.g., with cross-reactive micro-organisms in patients without thymoma ( 109 ) or be driven by acetylcholine receptor specific autoreactive helper CD4 + T cells in thymoma-associated myasthenia gravis where such autoreactive T cells have escaped tolerance mechanisms ( 110 , 111 ). Deficiency of IgM-NAA, especially IgM-NAA with anti-idiotypic activity to a specific IgG autoantibody, thus incompletely neutralizing the increase in pathogenic IgG autoantibodies, such as antibodies to neutrophil cytoplasmic enzymes (myeloperoxidase, proteinase 3), which are commonly referred to as ANCA, dsDNA, and glomerular basement membrane (GBM) that are present in normal individuals ( 31 , 50 , 87 , 112 ).…”
Section: Introductionmentioning
confidence: 99%
“…Excess production of a highly specific pathogenic IgG autoantibody by autoreactive B2 cell clones as, for example, in myasthenia gravis ( 108 ). Expansion of such B2 cell clones could have been driven by antigen, e.g., with cross-reactive micro-organisms in patients without thymoma ( 109 ) or be driven by acetylcholine receptor specific autoreactive helper CD4 + T cells in thymoma-associated myasthenia gravis where such autoreactive T cells have escaped tolerance mechanisms ( 110 , 111 ).…”
Section: Introductionmentioning
confidence: 99%
“…(4)(5)(6)(7)(8) Extensive review of the literature revealed cases of MG following viral infections. (9)(10)(11)(12)(13)(14)(15) This case, to the best of our knowledge, is the first reported case of MG following malaria infection.…”
Section: Introductionmentioning
confidence: 81%
“…A previous study raised the possibility of viral infection as etiological factor for myasthenia gravis and described five myasthenic patients, whose symptoms began a few weeks after a proven viral infection. (9) In addition, two cases of post-infectious myasthenia gravis were reported by Felice and colleagues in 2005 (10) ; a five year old boy who developed oculo-bulbar weakness two weeks following a varicellazoster infection and a four-year-old boy who developed facial diplegia and dysarthria several weeks following a viral pharyngitis. A third case was reported in 2007 by Saha et al representing the youngest, and second reported, case of post-varicella myasthenia gravis.…”
Section: Discussionmentioning
confidence: 99%